2015
DOI: 10.2169/internalmedicine.54.2348
|View full text |Cite
|
Sign up to set email alerts
|

Successful Recovery from an Acute Kidney Injury due to Amniotic Fluid Embolism

Abstract: A 33-year-old Japanese woman at 40 weeks gestation visited the maternity hospital after imminent labor had begun. After the delivery, persistent bleeding developed resulting in hemorrhagic shock. Although the hemorrhage was eventually controlled, hepatic and renal dysfunction occurred, leading to acute kidney injury (AKI). The patient's clinical presentation was suggestive of amniotic fluid embolism (AFE). We subsequently initiated continuous renal replacement therapy (RRT) for AKI. The patient's condition imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The neurological sequels are the most prevalent amniotic fluid complications reported in observational studies, affecting between 24% and 50% of cases [6,18,19]. The neurological sequels are closely followed by renal failure [20,21], cardiovascular and pulmonary disorders [22,23], or infectious complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…The neurological sequels are the most prevalent amniotic fluid complications reported in observational studies, affecting between 24% and 50% of cases [6,18,19]. The neurological sequels are closely followed by renal failure [20,21], cardiovascular and pulmonary disorders [22,23], or infectious complications [24].…”
Section: Discussionmentioning
confidence: 99%
“…Despite various treatments, AFE patients still have difficulty maintaining long-term physiological stability. At the time of referral to our hospital, 2 women had a body temperature below 35 °C, which may have been caused by severe hemorrhage and massive transfusion [18]. Hypothermia can lead to decreased thrombin activity, decreased platelet function, decreased fibrinogen synthesis, and increased fibrinolysis [19].…”
Section: Discussionmentioning
confidence: 99%
“…It is recommended that management be focused on resuscitation via intravascular volume repletion, correcting coagulopathy with appropriate blood products, controlling hemorrhage, administering inotropic and vasopressor support, as well as methods to prevent multi-organ dysfunction such as renal replacement therapy (RRT) [8]. Ihara et al suggested that RRT may filter fetal remnants of amniotic fluid from maternal circulation, thus provide renal protection and prevention of disease progression [10]. Additionally, other novel approaches have successfully been shown to treat AFE, including plasmapheresis, ventricular assist devices, intra-aortic balloon pump, and ECMO [1].…”
Section: Discussionmentioning
confidence: 99%